First European Biomedical Engineering Conference for Young Investigators ENCY2015, Budapest, May 28 - 30, 2015 - Jobbágy, Ákos (IFMBE Proceedings,, 2015)
This volume presents the proceedings of the first European Biomedical Engineering Conference for Young Investigators ENCY2015. It was in Budapest, from 28th to 30th May, 2015. The papers were assembled under the motto "Understanding complex living systems" and cover the topics sensors, image processing, bioinformatics, biomechanics, and modeling.